2014
DOI: 10.1371/journal.pone.0104429
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes Increase the Lipid Dynamics in the Leishmania Plasma Membrane at Concentrations Similar to Their IC50 Values

Abstract: Although many terpenes have shown antitumor, antibacterial, antifungal, and antiparasitic activity, the mechanism of action is not well established. Electron paramagnetic resonance (EPR) spectroscopy of the spin-labeled 5-doxyl stearic acid revealed remarkable fluidity increases in the plasma membrane of terpene-treated Leishmania amazonensis promastigotes. For an antiproliferative activity assay using 5×106 parasites/mL, the sesquiterpene nerolidol and the monoterpenes (+)-limonene, α-terpineol and 1,8-cineol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 39 publications
1
38
0
4
Order By: Relevance
“…Collectively, these results demonstrated that terpenes also cause the formation of two components in a cell membrane and that an increase in the terpene concentration leads to an increase in the population of the most dynamic spin probe component [16].…”
Section: Tablementioning
confidence: 69%
See 4 more Smart Citations
“…Collectively, these results demonstrated that terpenes also cause the formation of two components in a cell membrane and that an increase in the terpene concentration leads to an increase in the population of the most dynamic spin probe component [16].…”
Section: Tablementioning
confidence: 69%
“…Moreover, at their respective IC 50 values, these terpenes caused the lysis of 4 to 9% of cells, and this percentage reached up to approximately 50% at concentrations two to three times higher than the IC 50 values [16]. The IC 50 values of the sesquiterpene nerolidol and the monoterpenes (+)-limonene, α-terpineol and 1,8-cineole were 0.008, 0.549, 0.678 and 4.697 mM, respectively [16]. This result demonstrated that the in vitro cytotoxicity of nerolidol was similar to that of miltefosine, which is the first effective oral drug approved for the treatment of visceral and cutaneous leishmaniasis [32].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations